Dangerous Knowledge : The JFK Assassination in Art and Film - Simon, Art (Book collections on Project MUSE., 2012)
Fifty years ago, the assassination of John F. Kennedy shocked the world and focused attention to the 8mm footage shot by Abraham Zapruder. The event fueled conspiracy theories and repeated viewings of Zapruder's film as seemingly everyone in the world searched for motive and conclusive proof of a single gunman. In his new Preface to this edition of Dangerous Knowledge, Art Simon discusses public fascination with celebrity deaths and recent assassination-related media-from documentaries to scholarly books to the scandalous video game JFK Reloaded-to show that the assassinati.